Implementing and Sustaining Primary Health Care Accreditation Under Universal Health Coverage: A Qualitative Study in Indonesia: IN PRESS - Fadilah Aulia Rahma; Riswandy Wasir; Apriningsih Apriningsih; Suparni Suparni; Abdul Rahman Ramdzan (Jurnal Ilmu Kesehatan Masyarakat, 2026)
Under universal health coverage (UHC), improving access to services must be accompanied by strengthening service quality, particularly at the primary health care level. Accreditation has been widely adopted as a policy instrument to support quality improvement; however, evidence on its implementation and sustainability in primary health care remains mixed, especially in low- and middle-income countries. Objective: This study aimed to examine the implementation of primary health care accreditation and its implications for service quality under Indonesia’s UHC system. A qualitative descriptive study study was conducted in two fully accredited (Paripurna) primary health care centres (Puskesmas) in an urban setting in Indonesia. In-depth, semi-structured interviews were carried out with 17 participants, including managerial, clinical, and administrative staff, as well as representatives from professional health organisations. Data were analysed using framework-guided thematic analysis informed by the Donabedian model of health care quality. Five key themes were identified. Accreditation contributed to improved structural readiness, including facility organisation and documentation systems, and to greater standardisation of clinical and administrative processes through formalised quality governance. Effective implementation was enabled by leadership commitment, staff training, and professional support. However, accreditation was constrained by human resource limitations, administrative burden, and financial and infrastructural challenges. Sustaining quality improvements beyond accreditation surveys required integration of standards into routine management, continuous quality improvement practices, and the use of digital systems and external collaboration. Primary health care accreditation can support service quality improvement under UHC when effectively implemented and sustained. Its contribution depends on leadership, organisational capacity, and alignment with broader UHC policies. Strengthening these factors may enhance the role of accreditation as a sustainable quality improvement instrument in primary health care.